Room-Temperature Near-Infrared Electroluminescence from Boron-Diffused Silicon Pn-Junction Diodes - Li, Si; Gao, Yuhan; Fan, Ruixin; Li, Dongsheng; Yang, Deren (Frontiers in Materials, 2015)
Silicon pn junction diodes with different doping concentrations were prepared by boron diffusion into Czochralski (CZ) n-type silicon substrate. Their room-temperature near-infrared electroluminescence (EL) was measured. In the EL spectra of the heavily boron doped diode, a luminescence peak at ~1.6 m (0.78 eV ) was observed besides the band-to-band line (~1.1eV) under the condition of high current injection, while in that of the lightly boron doped diode only the band-to-band line was observed. The intensity of peak at 0.78 eV increases exponentially with current injection with no observable saturation at room temperature. Furthermore, no dislocations were found in the cross-sectional transmission electron microscopy image, and no dislocation-related luminescence was observed in the low-temperature photoluminescence spectra. We deduce the 0.78 eV emission originates from the irradiative recombination in the strain region of diodes caused by the diffusion of large number of boron atoms into silicon crystal lattice.